2017
DOI: 10.1074/jbc.m116.761882
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit distances in full-length, dimeric, bacterial phytochrome Agp1, as measured by pulsed electron-electron double resonance (PELDOR) between different spin label positions, remain unchanged upon photoconversion

Abstract: Bacterial phytochromes are dimeric light-regulated histidine kinases that convert red light into signaling events. Light absorption by the N-terminal photosensory core module (PCM) causes the proteins to switch between two spectrally distinct forms, Pr and Pfr, thus resulting in a conformational change that modulates the C-terminal histidine kinase region. To provide further insights into structural details of photoactivation, we investigated the full-length Agp1 bacteriophytochrome from the soil bacterium usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(48 reference statements)
2
12
1
Order By: Relevance
“…For example, the light-induced PHY separation revealed by Takala et al has not been observed in fulllength Agp1. 100,138 Although the existing full-length structures agree quite well with PSM structure when overlaid to corresponding PSM structures, 92,93 they generally show tighter packing of the PHY domains. Light activation leads to refolding of the PHY tongue, and we believe that this will also occur in full-length phytochromes.…”
Section: Perspectivementioning
confidence: 84%
See 1 more Smart Citation
“…For example, the light-induced PHY separation revealed by Takala et al has not been observed in fulllength Agp1. 100,138 Although the existing full-length structures agree quite well with PSM structure when overlaid to corresponding PSM structures, 92,93 they generally show tighter packing of the PHY domains. Light activation leads to refolding of the PHY tongue, and we believe that this will also occur in full-length phytochromes.…”
Section: Perspectivementioning
confidence: 84%
“…139 The opening movement has also not been observed in an EPR study on Agp1, where no major changes in between subunits were detected upon red illumination. 138 The 'rotation' model. In contrast to the 'opening' mechanism, X-ray solution scattering studies of DrBphP have indicated that the OPMs stay dimerized and that a twist of the histidine kinase OPM occurs with respect to the PSM when the phytochrome is photoactivated.…”
Section: Perspectivementioning
confidence: 99%
“…Light-induced refolding of the PHY tongue affects the orientation of the PHY domain, opening the entire PSM dimer (9). In full-length phytochromes, this large-scale change is then relayed by the long connecting helices to the output module, causing changes in its structure and activity (13)(14)(15). The output activity is often a kinase activity but may vary depending on the species, and its changes will lead to biological responses.…”
mentioning
confidence: 99%
“…Agp1‐M500‐K517C has two cysteines, one at position 20, to which the chromophore is covalently bound, and one at position 517. This mutant is described in an earlier publication . Agp2 has seven cysteines.…”
Section: Methodsmentioning
confidence: 99%